(untitled) (Scientific journal of the Fergana State University, 2025)
This research demonstrates the importance of engaging students in independent activities during the organization and implementation of physical education in general education schools. The school physical education team aims to educate students through physical exercises and sports activities, developing their management, leadership, and organizational skills. This process is one of the main tasks of school education and is aimed at increasing students’ life activity with the help of specialists in physical education and sports. According to the research results, effective organization of physical activities is crucially dependent on the participation of physical education instructors and sports specialists in the educational process. This approach creates the necessary conditions for students to spend their free time meaningfully and engage in physical exercises. Research conducted through monitoring confirms that such activities find their place in the education of young students and contribute to their active participation in society.